G51(P) A review of child sexual abuse (csa) reports. (27th April 2015) - Deepak, S; Teh, C; Adamson, L
Abstract : Background: Few areas of paediatrics have expanded so rapidly in clinical importance as that of sexual abuse of children. What Kempe called a "hidden paediatric problem"1 in 1977 is certainly less hidden at present. The NSPCC statistics April 2014 showed 1 in 20 children have been sexually abused. 5% of all the children on child protection registers or the subject of child protection plans in the UK were under a category of sexual abuse. Childhood sexual abuse has been correlated with long term morbidities like mental health problems and sexual and relationship problems. So this is a significant public health problem. Aim: We aimed to gain more knowledge on the CSA (child sexual abuse) examination findings in particular the anal findings, the demographics and to find out the prevalence of significant positive findings. Methodology: We carried out a retrospective analysis of CSA reports of children who underwent CSA examination during the 2 year period – April 2011 to April 2013. The electronic reports were accessed following formal permission from the trust. Findings: Majority of the children who underwent CSA examination are females (Figure 1 ). Only a small proportion of boys were examined. Most of the children were arranged to have the examination following disclosure (Table 1 ). Nearly half of the female children were noted to have some significant findings; however some of them were conclusive of sexual activity rather than abuse. Only 8.8% of children had positive anal findings and 54% had consistent history. Conclusion: Sexual abuse presents in many ways and because children who are sexually abused generally are coerced into secrecy, a high level of suspicion may be required to recognise the problem. Only a small proportion of children were noted to have clinical anal findings, so a detailed history taking is vital.